2014
DOI: 10.1155/2014/384706
|View full text |Cite|
|
Sign up to set email alerts
|

Transvaginal Appendectomy: A Systematic Review

Abstract: Background. Natural orifice transluminal endoscopic surgery (NOTES) is a new approach that allows minimal invasive surgery through the mouth, anus, or vagina. Objective. To summarize the recent clinical appraisal, feasibility, complications, and limitations of transvaginal appendectomy for humans and outline the techniques. Data Sources. PubMed/MEDLINE, Cochrane, Google-Scholar, EBSCO, clinicaltrials.gov and congress abstracts, were searched. Study Selection. All related reports were included, irrespective of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Whether patients have less postoperative pain needs to be further assessed in larger studies. A systematic review on vNOTES appendectomies reported a trend towards shorter hospitalisation, quicker recovery, less analgesic requirement and better cosmetic satisfaction [15]. A similar result can be expected for vNOTES salpingectomy.…”
Section: Discussionsupporting
confidence: 55%
“…Whether patients have less postoperative pain needs to be further assessed in larger studies. A systematic review on vNOTES appendectomies reported a trend towards shorter hospitalisation, quicker recovery, less analgesic requirement and better cosmetic satisfaction [15]. A similar result can be expected for vNOTES salpingectomy.…”
Section: Discussionsupporting
confidence: 55%
“…NOTES has gained popularity during recent years for less complex procedures such as cholecystectomy and appendicectomy. This is supported by evidence that when performed by appropriately trained surgeons the results can be favourable to that of conventional laparoscopic technique [ 7 , 25 ].…”
Section: Discussionmentioning
confidence: 88%
“…7,8 In addition to cholecystectomy, the transvaginal route can be used for appendectomy, colorectal resection, nephrectomy, sleeve gastrectomy, liver surgery, or incisional hernia repair. [7][8][9][10][11] The transanal route is used only for colorectal resections, and the transgastric route is mainly limited to cholecystectomy and appendectomy. 7,8,12 Here, we described three NOTES cholecystectomies through the jejunum, and to the best of our knowledge the small bowel as an access point for NOTES approaches has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%